Improving the performance of locally recruited Thai employees in a German software company - Mantalay N. (National Cheng Kung University, 2014)
Thailand's software development industry is growing rapidly and experiencing increased foreign direct investment. This paper presents a framework to help solve the problems faced by a German software firm when training and managing locally recruited Thai employees during their probationary period. Research results based on a mixed method case study are presented according to four steps: characterisation of issues affecting work quality, causality behind these issues, development of a personal mastery framework to tackle these issues, and finally, validation of this framework. Results show benefits for both employees and managers, with potential to reduce work quality issues and improve employees' creative tension and personal vision.